Estudo sobre parâmetros clínicos, fisiológicos e inflamatórios na sepse ou asma alérgica em proles submetidas a um modelo de hipotireoidismo gestacional experimental - Santos, Patricia Rabelo dos (2018)
The perinatal origin of the health-disease process in adult life has been focus of numerous studies. In this context, the adequate supply of maternal thyroid hormones for fetal development, in particular the immune system and, the increase of hypothyroidism gestational prevalence. The maternal hormones lack can be associated to many disorders on the offspring post-natal life. Despite, any study has investigated the influence of intrauterine microenvironment adverse in the susceptibility of offspring to sepsis and allergic asthma. Besides, there is no clinical score to evaluate the severity of sepsis in animal models, adapted and validated to Portuguese, such as the Murine Sepsis Score (MSS). Thus, clinical and physiological parameters of sepsis severity and the inflammatory response of allergic asthma in offspring submitted to Experimental Gestational Hypothyroidism (EGH) were evaluated. Simultaneously, the validation of the MSS to Portuguese was sought. EGH was induced by the administration of 0.02% methimazole in drinking water from the 9th gestational day until the day of delivery. Offspring of hypothyroid (OHM) and euthyroid (OEM) mothers underwent a sepsis model induced by cecal ligation and puncture (CLP) to assess survival, body temperature, severity and validation of MSS, or an ovalbumin-induced allergic asthma model (OIAA), to evaluate inflammatory parameters and oxidative stress. Data were expressed as mean ± SEM. Survival was estimated utilizing the Kaplan-Meier / LogRank test; body temperature and total scores were submitted to univariate analysis of variance (ANOVA) and Tukey post-test. For the study of the psychometric properties of the Brazilian Version of the Murine Sepsis Score (BV-MSS): the internal consistency was estimated by the Cronbach’s alpha (α) and Spearman coefficients; inter-valuer reliability was quantified by the intra-class correlation coefficient (ICC); the validity was investigated through binary logistic regression model, ROC curve and area under curve (AUC) quantification. Others analysis were done using a Two-way ANOVA, followed by the Bonferroni post-test. The critical level was set at 5%. There was no influence of EGH on the body mass of pregnant females during gestation (p = 0.19). The litter size in the 1st PND did not differ between euthyroid (EM) mothers and hypothyroid mothers (HM) (p = 0.7862). The offspring body mass at 7 and 14 PND was significantly lower in comparison to OHM males [7 PND: (p = 0,0057); 14 PND: (p = 0,0264)]. There was no difference between the survival curve (p = 0,66), body temperature (p = 0,90) and clinical score (p = 0,66) of OEM and OHM-Sepsis. OHM-OVA had lower leukocyte infiltration in bronchoalveolar lavage (BAL) (p <0.001), but the histological analysis of lung tissue did not showed this difference (p = 0.452); there was, also, lower myeloperoxidase activity in the lung (p <0.001) and lower eosinophil peroxidase content in BAL (p <0.05) compared to OEM - OVA. There was no influence of EGH on the concentration of Malondialdehyde and sulfhydryl content of the lung tissue. The BV-MSS presented excellent internal consistency (Cronbach's α = 0.945), inter-valuer reliability [ICC General Score = 0.922 (95% CI: 0.911 - 0.932)]. All correlations of the scale items were statistically significant (p <0.05). The overall score and mean score per item are significantly related to the probability of survival (p <0.05). The BV-MSS has excellent discriminatory power, AUC (95% CI) = 0.921 (0.878 - 0.965), p <0.0001 and great responsiveness. The score of 4.75 is the cut-off point (Youden's index = 0,741). Thus, it is concluded that EGH does not affect clinical and physiological parameters of septic animals, but demonstrates inhibitory effect on allergic lung inflammation of the offspring. In addition, the BV-MSS has excellent discriminatory performance, is highly reliable, replicable and valid for use in Portuguese-speaking countries to assess the clinical status of septic animals.